Type 1 diabetes mellitus, hyperlipidemia, and inflammatory bowel disease: a Mendelian randomization study - Xiangyin Liu; Yuming Li; Ruijie Lyu; Yanting Guo; Xianyong Yin; Jiajia Liu; Jing Wu (Acta Materia Medica)
Previous epidemiologic studies have shown a close association between type 1 diabetes mellitus (T1DM), hyperlipidemia, and inflammatory bowel disease (IBD), but the causal relationship has not been established. In the current study the causal relationships between T1DM and hyperlipidemia with IBD were assessed using Mendelian randomization (MR) analysis. A two-sample MR study was conducted utilizing accessible genome-wide association study data from public sources with the selection of suitable instrumental variables adhering to the principles of MR analysis. The primary technique utilized was the inverse variance weighted method, complemented by additional methods, such as MR-Egger regression, weighted median, simple mode, weighted mode, and the MR pleiotropy residual sum and outlier approach. Genetically determined T1DM had no causal relationship with IBD or IBD subtypes based on MR analysis. These findings were consistent across all supplementary methods used. In addition, genetically determined hyperlipidemia had no causal relationship with IBD or IBD subtypes, even after increasing the number of instrumental variables used. Our study supports the notion that there is no causal relationship between T1DM and IBD, as well as hyperlipidemia and IBD, which contradicts most observational studies.